Generalized anxiety disorder and worrying a comprehensive handbook for clinicians and researchers - Gerlach, Alexander 1966-; Gloster, Andrew T. 1974- (Wiley Blackwell, 2020)
"Everyone worries. Some people worry occasionally or transitorily, while others worry frequently or uncontrollably. The ubiquity of worry makes its study far-reaching, important, and exciting. Worry - like most concepts in mental health nomenclature - is not a technical term, however, but rather stems from everyday language's attempt to describe inner-psychic experiences. This, in turn, makes the study of worry difficult and sometimes messy. For example, if you simply ask a person to worry, will this instruction result in the same type of worry that is occurs naturally? Worrying at night, when trying to fall asleep is probably one of the most common situation in which people worry. However, why do we worry some nights and not others ? Is it really simply a question of triggers being responsible for a worry episode to start? Interestingly, in some treatments, asking individuals to worry is used therapeutically. This often results in the new experience that when one actively worries, it is actually less anxiety provoking and much less associated with a feeling of losing control than when worrying occurs spontaneously (compare Gerlach & Stevens, 2014)"--